Petrology and Geochemistry of Granitic Rocks from Macao - Dias, Ágata; Quelhas, P; Lou, U; Mata, J; Ribeiro, M L (Goldschmidt, 2016)

New geochemical constraints on I-type granites of Macao: evidences for fractional crystallization and petrogenetic affinities with Jurassic-Cretaceous granites in SE China - Dias, Ágata; Quelhas, P; Mata, J; Lou, U T; Borges, R; Ribeiro, M. L (Goldschmidt, 2017)

Mesozoic Granitic Magmatism in Macao, Southeast China - Quelhas, P. M.; Mata, J.; Lou, U. T.; Ribeiro, M. L.; Dias, Ágata (AGU Fall Meeting Abstracts, 2016)
Macao ( 30 Km2) is a territory characterized by small granitic intrusions, located along the coastal region of Southeast China (Cathaysia Block). Granitoids occur as different facies, including microgranite dykes, with distinct textural, mineralogical and geochemical features, for which a middle-upper Jurassic age ( 164 Ma) has been proposed. New data suggest that these granitoids are mostly high-K calc-alkaline metaluminous (A/CNK = 0.8 - 1.1) biotite granites, consistent with total absence of primary muscovite. They show variable amounts of SiO2 (67-77%), reflecting different degrees of magmatic evolution. There is also variability in terms of trace elements, particularly Rare Earth Elements (REEs), evidenced by decreasing (La/Sm)N, (Gd/Lu)N, (Ce/Yb)N and (Eu/Eu*)N towards the more evolved samples, which can be partly attributed to fractional crystallization processes. Most of the granitoids are characterized by (La/Yb)N = 3 - 10.8, showing negative Ba, Nb, Sr, Zr, P, Ti and Eu anomalies. On the other hand, microgranite dykes, along with a few more evolved granites, show an opposite tendency, being usually enriched in HREEs relatively to LREEs with (La/Yb)N = 0.4 - 1.1. Our data suggests intermediate genetic affinities between I-type and A-type granites. Although these granitoids are mostly metaluminous (characteristic of I-types), Ga/Al ratios, usually used to identify A-types, are close to the accepted boundary between A-type and other granite types. The affinities with A-type granites are more marked for the more evolved facies, which depict higher values of FeOt/MgO (14 - 60) and K2O/MgO (60 - 250). Their trace element characteristics are also transitional between WPG (Within-plate granites) and Syn-COLG (Collision Granites). We interpret those transitional characteristics (A/I and WPG/Syn-COLG) of Macao granitoids as reflecting an origin by melting of infracrustal sources over a period of high heat transfer from mantle to crust during an extensional tectonic setting probably contemporaneous with the subduction of the paleo-Pacific plate beneath the Eurasia, whose paleo-suture is thought to be located in the east flank of the Central Range, Taiwan.
Keywords: 8499 General or miscellaneous; VOLCANOLOGY

A origem e evolução dos magmas graníticos de Macao à luz de dados de geoquímica elementar e isotópica / Source and evolution of Macao granitic magmas: insights from wholerock geochemistry and isotopic signatures. - Dias, Ágata; Quelhas, P; Mata, J; Lou, U T; Ribeiro, M L; Borges, R (XIV Congresso de Geoquímica dos Países de Língua Portuguesa e XIX Semana de Geoquímica (XIV CGPLP/XIX SG, international conference, 2018)